UTEM Publisher visits UMP Publisher office - Shalfarina, Shahriman (Penerbit UMP, 2014)
The success story of Universiti Malaysia Pahang (UMP)'s digital book publication, e-Book and the product generating income for the university attracted the attention of Universiti Teknikal Melaka (UTeM) Publisher. The university expressed their interest to work together with UMP Publisher.